Dampak Pernikahan Dini Terhadap Pendidikan Bagi Remaja di Desa Waiara Kecamatan Kewapante Kabupaten Sikka - Trisnawati Bura; Nona Lin; Natalia Mercyana; Yusfina Tuto (Populer: Jurnal Penelitian Mahasiswa, 2025)
Early marriage is a social phenomenon that occurs a lot among teenagers, especially in rural areas such as Waiara Village, Kewapante Subdistrict. Early marriage is still a social problem that is often found in various regions, including in Waiara Village, Kewapante Subdistrict. This study aims to examine the effect of early marriage on adolescent education. The approach used was qualitative through in-depth interviews with teenagers who married young, their parents and educators in the village. The research findings revealed that early marriage has a negative impact on adolescents' education, such as increased dropout rates, low levels of engagement in further education and decreased motivation to learn. In addition, the huge responsibilities that come with early marriage often make adolescents focus more on household affairs than education. This study recommends government and community interventions to increase understanding of the importance of education and the adverse effects of early marriage